2017
DOI: 10.1017/s1041610217001181
|View full text |Cite
|
Sign up to set email alerts
|

Attended With and Head-Turning Sign can be clinical markers of cognitive impairment in older adults

Abstract: AW and HTS are fast, simple, effective, and sensitive methods for detecting CI. Therefore, they can be used for older adults attending the primary care settings with memory loss. Those with positive AW or HTS can be referred to the relevant centers for detailed cognitive assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 25 publications
3
39
1
Order By: Relevance
“…In our clinic, we found that HTS is not sensitive but very specific for cognitive impairment (hence, low false positive rate but high false negative rate) with high positive predictive value (Table 1). These findings are consistent across our two patient cohorts, but contrast with the findings of Soysal et al (2017), who found HTS to have high sensitivity and negative predictive value for cognitive impairment. The reasons for this discrepancy are not immediately apparent to us, but may possibly relate to methodological factors (HTS may be defined differently in different studies Tabuas-Pereira et al (2016)) or cultural factors (HTS had a higher frequency in the Soysal et al cohort, 244/369 = 66.1% of AW).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In our clinic, we found that HTS is not sensitive but very specific for cognitive impairment (hence, low false positive rate but high false negative rate) with high positive predictive value (Table 1). These findings are consistent across our two patient cohorts, but contrast with the findings of Soysal et al (2017), who found HTS to have high sensitivity and negative predictive value for cognitive impairment. The reasons for this discrepancy are not immediately apparent to us, but may possibly relate to methodological factors (HTS may be defined differently in different studies Tabuas-Pereira et al (2016)) or cultural factors (HTS had a higher frequency in the Soysal et al cohort, 244/369 = 66.1% of AW).…”
supporting
confidence: 89%
“…In our studies, we focused on the "Attended Alone" (AA) sign as a marker of cognitive health, rather than AW as a marker of cognitive impairment. Re-examining our data (Larner, 2014), we present (Table 1) our findings for AW, rather than AA, for ease of comparison with the findings of Soysal et al (2017).…”
mentioning
confidence: 99%
“…The neurological signs examined are non-canonical, and currently not widely used (with the possible exception of the applause sign, particularly in the context of movement disorder clinics), although potentially widely applicable, since they are quick to perform, cost free, and easily interpreted and categorised. Some validation studies in independent patient cohorts have been reported for some of these signs [ 19 , 20 ], but studies of possible relationships to disease biomarkers are in their infancy [ 21 ]. The signs examined are easily dichotomised, thus facilitating calculation of NND, NNP, and NNM, which may not be the case for cognitive screening instruments which require the application of test cut-offs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…They may affect treatment decisions and help identify high‐risk individuals. The attended alone sign (AAS), head‐turning sign (HTS), and applause sign (AS) have separately been reported as evidence of CI or underlying neurodegenerative diseases …”
Section: Introductionmentioning
confidence: 99%
“…Each of these signs has been previously evaluated in a limited number of studies, but the effectiveness of using these signs in combination in a large number of older adults with or without CI has not been evaluated . Moreover, these signs have not been studied in different locations and cultures.…”
Section: Introductionmentioning
confidence: 99%